An atypical case of Noonan syndrome with mutation diagnosed by targeted exome sequencing - Jinsup Kim; Sung Yoon Cho; Aram Yang; Ja-Hyun Jang; Youngbin Choi; Ji-Eun Lee; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2017)
Noonan syndrome (NS) is a genetic disorder caused by autosomal dominant inheritance and is characterized by a distinctive facial appearance, short stature, chest deformity, and congenital heart disease. In individuals with NS, germline mutations have been identified in several genes involved in the RAS/mitogen-activated protein kinase signal transduction pathway. Because of its clinical and genetic heterogeneity, the conventional diagnostic protocol with Sanger sequencing requires a multistep approach. Therefore, molecular genetic diagnosis using targeted exome sequencing (TES) is considered a less expensive and faster method, particularly for patients who do not fulfill the clinical diagnostic criteria of NS. In this case, the patient showed short stature, dysmorphic facial features suggestive of NS, feeding intolerance, cryptorchidism, and intellectual disability in early childhood. At the age of 16, the patient still showed extreme short stature with delayed puberty and characteristic facial features suggestive of NS. Although the patient had no cardiac problems or chest wall deformities, which are commonly present in NS and are major concerns for patients and clinicians, the patient showed several other characteristic clinical features of NS. Considering the possibility of a genetic disorder, including NS, a molecular genetic study with TES was performed. With TES analysis, we detected a pathogenic variant of c.458A > T in KRAS in this patient with atypical NS phenotype and provided appropriate clinical management and genetic counseling. The application of TES enables accurate molecular diagnosis of patients with nonspecific or atypical features in genetic diseases with several responsible genes, such as NS.